The Pretkalpa of the Garuda Mahapurana as a Reflection of Social History: A Sociological Study of Soul Purification - Shukra Raj Adhikari; Bhawani Shankar Adhikari; Ganga Acharya; Nisha Pradhananga (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: This article examines the Pretkalpa of the Garuda Mahapurana as a source for understanding the moral imagination and social values of ancient Sanatani society. It focuses on the concepts of soul purification, karma, rebirth, heaven, hell, and posthumous reward and punishment as reflected in the text. Using a qualitative design and historical content analysis, this study interprets selected passages from the Garuda Mahapurana to explore how the text constructs ethical order and explains the consequences of human action. The findings show that the Pretkalpa presents the soul as immortal and places human life at the center of moral choice, where virtuous action leads to purification and favorable rebirth, while sinful conduct results in suffering, hell, and lower forms of existence. The text also portrays fear of punishment and hope of reward as important mechanisms for guiding human behavior. This study argues that the Garuda Mahapurana can be read not only as a religious scripture but also as a reflection of social history, because it preserves ideas about morality, ritual practice, and social control in the Puranic period. The article contributes to the study of ancient texts by showing how scriptural narratives functioned as ethical guides within historical society. Abstrak: Artikel ini mengkaji Pretkalpa dalam Garuda Mahapurana sebagai sumber untuk memahami imajinasi moral dan nilai-nilai sosial masyarakat Sanatani kuno. Kajian ini berfokus pada konsep pemurnian jiwa, karma, kelahiran kembali, surga, neraka, serta ganjaran dan hukuman setelah kematian sebagaimana tercermin dalam teks tersebut. Dengan menggunakan desain kualitatif dan analisis isi historis, penelitian ini menafsirkan bagian-bagian terpilih dari Garuda Mahapurana untuk mengeksplorasi bagaimana teks tersebut membangun tatanan etis dan menjelaskan konsekuensi dari tindakan manusia. Temuan penelitian menunjukkan bahwa Pretkalpa memandang jiwa sebagai sesuatu yang abadi dan menempatkan kehidupan manusia sebagai pusat pilihan moral, di mana tindakan kebajikan mengarah pada pemurnian dan kelahiran kembali yang lebih baik, sedangkan perbuatan dosa berujung pada penderitaan, neraka, dan bentuk keberadaan yang lebih rendah. Teks ini juga menggambarkan rasa takut terhadap hukuman dan harapan akan ganjaran sebagai mekanisme penting dalam membimbing perilaku manusia. Penelitian ini berargumen bahwa Garuda Mahapurana tidak hanya dapat dibaca sebagai kitab keagamaan, tetapi juga sebagai refleksi sejarah sosial, karena memuat gagasan tentang moralitas, praktik ritual, dan kontrol sosial pada periode Puranik. Artikel ini berkontribusi pada kajian teks-teks kuno dengan menunjukkan bagaimana narasi kitab suci berfungsi sebagai pedoman etis dalam masyarakat.